Inhibiting glycosphingolipids alleviates cardiac hypertrophy by reducing reactive oxygen species and restoring autophagic homeostasis - Jiang, Chunxin; Tan, Menglei; Lai, Lunmeng; Wang, Yanping; Chen, Zijun; Xie, Qing; Li, Yunsen (Frontiers in Pharmacology, 2024)
Introduction Cardiac hypertrophy is a compensatory stress response produced by a variety of factors, and pathologic hypertrophy can lead to irreversible, severe cardiac disease. Glycosphingolipids (GSLs) are vital constituents of cells, and changes in their content and composition are important factors causing mitochondrial dysfunction in diabetic cardiomyopathy; however, the relationship between GSLs expression and cardiac hypertrophy and specific mechanisms associated with it are not clear. Methods Here, using male C57BL/6 mice, we performed aortic arch reduction surgery to establish an animal model of pressure overload cardiac hypertrophy. In addition, phenylephrine was used in vitro to induce H9c2 cells and neonatal rat left ventricular myocytes (NRVMs) to establish a cellular hypertrophy model. Results Mass spectrometry revealed that the composition of GSLs was altered in pressure overload-induced hypertrophied mouse hearts and in stimulated hypertrophied cardiomyocyte cell lines. Specifically, in both cases, the proportion of endogenous lactosylceramide (LacCer) was significantly higher than in controls. Inhibition of GSL synthesis with Genz-123346 in NRVMs reduced cell hypertrophy, as well as fibrosis and apoptosis. By Western blotting, we detected decreased intracellular expression of Sirt3 and elevated phosphorylation of JNK after phenylephrine stimulation, but this was reversed in cells pretreated with Genz-123346. Additionally, increased protein expression of FoxO3a and Parkin, along with a decreased LC3-II/I protein ratio in phenylephrine-stimulated cells (compared with unstimulated cells), indicated that the mitochondrial autophagy process was disrupted; again, pretreatment with Genz-123346 reversed that. Discussion Our results revealed that changes in GSLs in cardiomyocytes, especially an increase of LacCer, may be a factor causing cellular hypertrophy, which can be alleviated by inhibition of GSLs synthesis. A possible mechanism is that GSLs inhibition increases the expression of Sirt3 protein, scavenges intracellular reactive oxygen species, and restores mitochondrial autophagy homeostasis, thereby lessening cardiomyocyte hypertrophy. In all, these results provide a new perspective for developing drugs for cardiac hypertrophy.